Modelling light: the transformative role of the model and the miniature studio in the development of lighting design practices in the UK. Issue 1 (3rd April 2018) - Hunt, Nick
ABSTRACT: As a plastic, immaterial medium, the use of light on stage is challenging: how to experiment, test, develop and communicate lighting intentions in advance of the performance? How, in other words, to model light? And for lighting practitioners, how to acquire, hone and reinvent techniques and a design sensibility? Lit models have been used for these purposes since at least the start of the twentieth century, working at various scales from the traditional 1:24 or 1:25 of the scenic designer's model up to room-sized, quarter-scale model studios. In this article, I trace the crucial role of model-scale lighting and miniature lighting rigs in the development of lighting practice in the UK at key historical moments: in the 1950s when the named role of lighting designer first appeared; in the 1990s when dedicated degree-level lighting design education began and when the model studio concept initiated the practice of pre-visualisation and pre-programming of lighting for the concert stage, before the advent of 3D software visualisation. I argue these developments were vital to the establishment of performance lighting in the UK as an artistic practice in its own right, and propose the model-scale lighting studio has a continuing role for lighting designers' development.